Teaching Tolerance in a Globalized World - Sandoval-Hernández, Andrés; Isac, Maria Magdalena; Miranda, Daniel (IEA Research for Education, 2018)
Attitudes towards diversity; International large-scale assessment; International Civic and Citizenship Study; ICCS; Comparative and international education; School segregation; Intergenerational transmission of inequality; Open classroom for discussion; Measurement invariance; Multilevel Structural Equation Modelling; Tolerance